Implementasi Program Pusat Pelayanan Keluarga (Pusaka) Sakinah Di Kantor Urusan Agama (Kua) Kecamatan Somba - Wahyuni, Wahyuni; Razak, Andi Rosdianti; Parawangi, Anwar (Universitas Muhammadiyah Makassar, 2021)
This study aimed to find out the implementation and supporting and inhibiting factors of the Family Service Center Sakinah Program at Religious Affairs Office (KUA) Somba Opu Sub-District, Gowa Regency . This study used qualitative research with descriptive type. The data was collected and then analyzed based on indicators. The results showed that the Sakinah program put the headman as the vanguard. In the interpretation aspect, it showed that the technical guidance given in accordance with the technical guidelines for the Sakinah heritage program. Then, application aspects showed a program focused on family resilience. The supporting factor was human resources qualified and supported from the central government while the inhibiting factor were close minded and less awareness about the importance of this program. Keywords: Implementation, Service, Religious Affairs Office (KUA).